2007
DOI: 10.1074/jbc.m700936200
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin Adaptor GGA1 Polymerizes Clathrin into Tubules

Abstract: GGAs, a class of monomeric clathrin adaptors, are involved in the sorting of cargo at the trans-Golgi network of eukaryotic cells. They are modular structures consisting of the VHS, the GAT, hinge, and GAE domains, which have been shown to interact directly with cargo, ARF, clathrin, and accessory proteins, respectively. Previous studies have shown that GGAs interact with clathrin both in solution and in the cell, but it has yet been shown whether they assemble clathrin. We find that GGA1 promoted assembly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…GGAs are a family of monomeric clathrin adaptors that mediate the sorting of transmembrane cargo from the trans-Golgi network to late endosomes [48]. GGA1 can directly interact with clathrin [49-51], AP1 [52,53], ARF [54], Rabaptin-5 [55,56] and with a variety of cargo molecules [57], and is required for sorting of the lysosomal targeting receptor, mannose-6-phosphate receptor [48,52]. It has also been observed that overexpression of GGA3 inhibits retrovirus assembly [58], and that the molecule interacts with TSG101, an ubiquitin-binding component of the multivesicular body that is a key regulator of HIV budding.…”
Section: Discussionmentioning
confidence: 99%
“…GGAs are a family of monomeric clathrin adaptors that mediate the sorting of transmembrane cargo from the trans-Golgi network to late endosomes [48]. GGA1 can directly interact with clathrin [49-51], AP1 [52,53], ARF [54], Rabaptin-5 [55,56] and with a variety of cargo molecules [57], and is required for sorting of the lysosomal targeting receptor, mannose-6-phosphate receptor [48,52]. It has also been observed that overexpression of GGA3 inhibits retrovirus assembly [58], and that the molecule interacts with TSG101, an ubiquitin-binding component of the multivesicular body that is a key regulator of HIV budding.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Sec13/31 tubule is well suited for binding Sec23/24 and a tubular membrane despite blocking some of the Sec23/24 binding sites on individual Sec13/31 heterotetramers. Interestingly, in the endocytic pathway, clathrin has also been shown to polymerize into tubules in the presence of the GGA adaptor molecule (Zhang et al, 2007). Analogously, it is possible in the COPII system that Sec23/Sec24, in combination with TANGO1 and procollagen, promote the formation of a Sec13/31 tubular carrier in vivo, though this hypothesis would be quite difficult to test experimentally.…”
Section: Model For the Assembly Of The Sec13/31 Tubulementioning
confidence: 95%
“…Instead, uncharacteristic coated pits were seen in close association with the PVs (10), suggesting that a distinct arrangement of clathrin might occur in this parasite. It is also possible that, as was observed in vitro (35), clathrin may be organized in a hexagonal array, forming tubes instead of vesicles. Similar to TCs in HeLa cells (26), the tubules might not break down into CCVs en route to PVs in Giardia.…”
Section: Clathrin and Adaptor Proteinsmentioning
confidence: 99%